Lirik Lagu “Citra Cinta” Karya Rhoma Irama: Kajian Stilistika - Moh Muzakka (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2021)
The purpose of this research is to study the language style of Rhoma Irama's song lyrics entitled "Citra Cinta". To study these lyrics, stylistic theory is used, which is an interdisciplinary linguistic theory whose object of study is literary works. The work steps used in this study are to apply stylistic work steps initiated by Pradopo, namely analyzing language style based on the units that build literary works, namely sound style, word style, sentence style, and discourse style. The results of the analysis show that the language style that builds the lyrics of the song "Citra Cinta" by Rhoma Irama cannot be separated independently because the lyrical discourse of the song is built by a coherent sound style, word style, and sentence style to build the discourse,  namely the value of love that is holy and noble.